Exploring Cultural Factors in Counseling: Experiences of Broaching Behaviors among Professional Counselors - Seto, Atsuko; Nagarajan, Sudha; Badrinath, Anjali (International Journal of Multicultural Counseling and Development, 2025)
A growing body of literature on broaching supports its effectiveness and addresses some challenges for applying this method to counseling practice. A thematic analysis with a phenomenological perspective was used to explore counselors’ experiences with broaching in their clinical practice to gain a greater understanding of its actual implementations in counseling. Four themes were identified through analysis of semi-structured interviews with five participants. They are: 1) demonstrating social justice and advocacy orientation as a foundation for broaching; 2) acknowledging the role of counselor self-disclosure in broaching; 3) contextual nature of broaching; and 4) commitment to engaging in ongoing development of broaching skills.